HUBUNGAN ANTARA MEDIA PEMBELAJARAN DAN SIKAP SISWA DALAM PEMBELAJARAN MATEMATIKA BERBASIS DATA TIMSS (Jurnal Teknodik, 2018)
Indonesian students’ Mathematics learning Achievement which is internationally measured through TIMSS is still very low. Their attitudes are highly influenced by the attractiveness or not the teaching-learning activities in the class. One of the students’ interest in the teaching-learning activities in the class is the availability of learning media. The objective of this study is to find out the correlation between the students attitudes and the learning media. The data used for this study is the TIMSS data of 2011 which is the result of the questionnaire consisting of 25 questions on students’ attitudes and 5 questions on learning media. The samples are the participants of TIMSS 2011 for Mathematics which is amounting of 5.795 students of 8th grade from all over Indonesia. Students’ Mathematics learning attitudes meant here are students’ interest in Mathematics, their appreciation to Mathematics, and their confidence on Mathematics as well as its usage in their life. The result shows that there is a positive and significant correlation between students’ interest on Mathematics, their appreciation to Mathematics as well as to the teacher, their confidence on their competence on Mathematics as well as its usage, and the learning media (computer, computer software, and audio-video media). For calculator media, it has correlation only with few questions. The interesting thing in this study is that the media used by the teacher is highly correlated with students’ attitudes in learning Mathematics as well as in understanding its usage in their life and their future.Hasil belajar Matematika siswa Indonesia yang diukur secara internasional melalui TIMSS masih sangat rendah.Sikap siswa sangat dipengaruhi oleh menarik-tidaknya kegiatan pembelajaran di kelas. Salah satu hal yang menarik siswa adalah ketersediaan media pembelajaran. Dalam kaitan ini, peneliti mencoba mencari hubungan antara sikap siswa dengan media pembelajaran di sekolah. Data yang digunakan adalah data TIMSS 2011 yang berupa data hasil angket kuesioner yang terdiri dari 25 pertanyaan tentang sikap dan 5 pertanyaan tentang media. Sampel dalam penelitian ini adalah peserta TIMSS 2011 untuk mata pelajaran Matematika yang berjumlah 5795 orang siswa kelas VIII perwakilan dari seluruh Indonesia. Sikap belajar Matematika yang dimaksudkan dalam penelitian ini adalah kesukaan siswa terhadap Matematika, sikap menghargai Matematika, serta kepercayaan diri siswa terhadap kemampuan matematikanya dan kegunaannya untuk kehidupannya dan masa depannya. Hasil analisis menunjukkan adanya korelasi positif dan signifikan antara perasaan senang atau suka belajar Matematika, sikap menghargai pelajaran Matematika dan gurunya, serta rasa percaya diri terhadap kemampuannya dan kegunaan Matematika dengan media pembelajaran (komputer, perangkat lunak komputer, dan media audio visual). Untuk media kalkulator, hanya berkorelasi pada sebagian kecil dari item yang ditanyakan. Hal yang menarik dari penelitian ini adalah bahwa media yang digunakan guru sangat berhubungan dengan sikap siswa dalam belajar Matematika dan memahami kegunaan Matematika untuk kehidupannya dan masa depannya.